2015
DOI: 10.1186/s12911-015-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling antecedents of electronic medical record system implementation success in low-resource setting hospitals

Abstract: BackgroundWith the increasing implementation of Electronic Medical Record Systems (EMR) in developing countries, there is a growing need to identify antecedents of EMR success to measure and predict the level of adoption before costly implementation. However, less evidence is available about EMR success in the context of low-resource setting implementations. Therefore, this study aims to fill this gap by examining the constructs and relationships of the widely used DeLone and MacLean (D&M) information system s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 33 publications
10
72
2
Order By: Relevance
“…Theoretical frameworks and technology adoption models were applied and tested in several studies. One provided empirical data about the relevance of the DeLone and MacLean (D&M) information system success model in the context of EMR implementation in low‐resource settings . The D&M model is one of the most widely accepted and used models for assessing success of information systems.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Theoretical frameworks and technology adoption models were applied and tested in several studies. One provided empirical data about the relevance of the DeLone and MacLean (D&M) information system success model in the context of EMR implementation in low‐resource settings . The D&M model is one of the most widely accepted and used models for assessing success of information systems.…”
Section: Resultscontrasting
confidence: 65%
“…One provided empirical data about the relevance of the DeLone and MacLean (D&M) information system success model in the context of EMR implementation in low-resource settings. 16 The D&M model is one of the most widely accepted and used models for assessing success of information systems. The constructs and relationships from the updated D&M model were found applicable for assessing the success of EMRs in low-resource settings.…”
Section: Testing Theoretical and Conceptual Models For Ehr Implemenmentioning
confidence: 99%
“…This variable is used to measure the desired characteristics of the system [13]. Previous studies have shown that system quality has an influence on user satisfaction [11], [14].…”
Section: B Research Variablesmentioning
confidence: 99%
“…The demands placed on healthcare professionals and organizations to deliver timely and cost effective healthcare services have resulted in the increased adoption of Health Information Systems (HIS) on a global scale (Tilahun & Fritz, 2015). Defined as "any system that captures, stores, manages or transmits information related to the health of individuals or the activities of organizations that work within the health sector" (Aghajari, Hassankhani, & Shaykhalipour 2013, p. 536), HIS are changing how healthcare services are being delivered, with the World Health Organisation listing HIS as a key building block for strong health systems (World Heallth Organization, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Defined as "any system that captures, stores, manages or transmits information related to the health of individuals or the activities of organizations that work within the health sector" (Aghajari, Hassankhani, & Shaykhalipour 2013, p. 536), HIS are changing how healthcare services are being delivered, with the World Health Organisation listing HIS as a key building block for strong health systems (World Heallth Organization, 2007). As a result, many international and humanitarian agencies are investing vast amounts of money to improve HIS in developing countries (Tilahun & Fritz, 2015). This stems from the expectation that successfully implemented HIS have the ability to transform healthcare delivery.…”
Section: Introductionmentioning
confidence: 99%